Ecological School-Based Group Counselling for Enhancing Mental Health of Migrant Adolescents in Kinabalu, Malaysia - Laila Meiliyandrie Indah Wardani; Rika Fitriyana; Kus Hanna Rahmi; Siti Urbayatun; Mohd. Dahlan Abdul Malek (Smart Society, 2026)
Migrant adolescents in school settings often face emotional, social, and academic challenges related to adaptation and future uncertainty. This study examines how an ecological school-based group counselling program implemented at Sekolah Indonesia Kota Kinabalu, Malaysia, contributes to participants’ reported experiences of resilience and adaptive coping among migrant adolescents. Using a qualitative descriptive design, the study involved 25 migrant students aged 15–17 years who were purposively selected based on indications of emotional, academic, and psychosocial difficulties identified during the school needs assessment process.  The intervention consisted of a single counselling session deliveres concurrently to four parallel groups of students. Data were collected through session documentation, facilitator observations, and student reflective notes, and analyzed using thematic analysis. The findings revealed three main themes: (1) emotional regulation and expression, where students developed greater awareness and control over their emotions; (2) peer connectedness and social support, reflected in reduced feelings of isolation and increased sense of belonging; and (3) future orientation and adaptive coping, indicated by improved problem-solving skills and more constructive perspectives toward life challenges. These findings suggest positive changes in participants’ psychosocial well-being, particularly in emotional stability, social connectedness, and adaptive coping. The novelty of this study lies in its application of an ecological group counselling framework within a migrant school context, integrating individual, peer, and systemic dimensions of intervention, which remains underexplored in previous research predominantly focused on individual counselling approaches. Future implementation should focus on developing standardized ecological group counselling modules, strengthening teacher capacity in psychosocial support, and scaling up school-based mental health programs through policy integration to better serve migrant student populations.